Climate change vulnerability and mobility among children and youth in Ethiopia: Current policy dilemmas and recommendations - Tekalign Ayalew Mengiste; Ninna Nyberg Sørensen (Danish Institute for International Studies (DIIS), 2021)
All over the world, people are feeling the effects of unprecedented, intensifying and in some instances irreversible climate change. Those growing up in developing countries are particularly vulnerable to these changes. This report focuses on how children and youth in Ethiopia, a country with well-established traditions of migration, experience and respond to severe climate-change impacts. The report draws attention to the complex ways in which climate change interacts with other factors driving migration. It shows that human mobility may constitute a viable adaptation strategy to slow-onset climate change, whereas extreme weather events tend to lead to significant human displacements, often with severe consequences for the ability of children and young people to establish viable futures. Based on available research and policy analysis, the report summarises existing knowledge on the relationships between vulnerability to climate change, child and youth mobility, and child- and youth-sensitive mechanisms of social protection with the aim of identifying the main policy dilemmas confronting policy-makers and practitioners.
Keywords: 300